2011
DOI: 10.1029/2011jc007006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mesoscale processes to nutrient budgets in the Arabian Sea

Abstract: [1] We examine the impact of mesoscale dynamics on the seasonal cycle of primary production in the Arabian Sea with an eddy-resolving (1/12°) bio-physical model. Comparison with observations indicates that the numerical model provides a realistic description of climatological physical and biogeochemical fields as well as their mesoscale variability during the Southwest and Northeast Monsoons. We show that mesoscale dynamics favors biological production by modulating the nutrient supplies throughout the year. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 123 publications
(148 reference statements)
5
117
3
Order By: Relevance
“…This is in agreement with previous work by Resplandy et al (2011) that showed that when the thermocline is anomalously shallow, as along the western coasts of the Arabian Sea in summer, the atmospheric forcing combined with vertical processes will produce strong cooling and a strong biomass response.…”
Section: Model Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with previous work by Resplandy et al (2011) that showed that when the thermocline is anomalously shallow, as along the western coasts of the Arabian Sea in summer, the atmospheric forcing combined with vertical processes will produce strong cooling and a strong biomass response.…”
Section: Model Resultssupporting
confidence: 82%
“…This is shown in Figure 15, when a snapshot from REG, of the relative vorticity and horizontal velocities at the surface in August shows such eastward movement. Despite the model resolution, it is also clear that in the model the eastward transport is mediated by mesoscale structures, in the form of eddies and elongated filaments, in agreement with previous works (Dickey et al, 1998;Kawamiya, 2001;Resplandy et al, 2011). …”
Section: Model Resultssupporting
confidence: 75%
“…Our results also contrast with those in Resplandy et al (2011). The focus in Resplandy et al (2011) is on the productivity driven by horizontal and vertical advection in summer and mostly vertical advection in winter.…”
Section: Blooms In Mesoscale Structurescontrasting
confidence: 56%
“…Although Gaube et al (2014) find a negative correlation between chlorophyll and SSH in the Arabian Sea, they do not analyze which of these mechanisms is involved in this region, nor do they quantify the extent to which this correlation varies over the course of the season. Resplandy et al (2011) indicated that the spatial variability associated with mesoscale eddies in the Arabian Sea produces spatial variability in the bloom and that another source of variability is found to be restratification at these structures. Advection from coastal region is identified as the mechanism providing nutrients in summer, while vertical velocities associated with mesoscale structure are found to increase the overall nutrient supply.…”
mentioning
confidence: 99%
“…However, the observations in this region have been derived from a local model fit to observed sediment properties (Luff et al, 2000), which may not correspond to assumptions inherent in the global model used in this study. In addition, mesoscale processes are not resolved in our coarse, 1 • × 1 • model, but their representation has been shown to be very important in this region (Kawamiya, 2001;Resplandy et al, 2011). Global z level models often fail to represent the complex hydrodynamic and biogeochemical structures of the Arabian Sea (Dietze, personal communication, 2013).…”
Section: Benthic Remineralizationmentioning
confidence: 99%